Black phosphorus quantum dots facilitate carrier separation for enhancing hydrogen production over hierarchical Cu7S4/ZnIn2S4 composites. Issue 4 (17th January 2020) - Zhang, Quan; Zhang, Juhua; Zhang, Lu; Yang, Fengli; Li, Lingfeng; Dai, Wei-Lin
Abstract : Efficient charge separation of Cu7 S4 /ZnIn2 S4 and the carrier transfer facilitator of BPQDs are responsible for the enhanced H2 production, resulting in the H2 evolution rate of 885 μmol g −1 h −1, 6.8 times higher than that of pristine ZnIn2 S4 . Abstract : At present, inefficient charge separation is considered to be one of the most important factors, limiting the photocatalytic hydrogen production. To solve this problem, herein, hierarchical Cu7 S4 /ZnIn2 S4 decorated with black phosphorus quantum dots (BPQDs) was rationally designed and its photocatalytic hydrogen evolution was investigated under visible light. The structural characterization proved the wrapped morphology of ZnIn2 S4 grown on the Cu7 S4 nanocrystals and BPQDs were uniformly dispersed on the surface of ZnIn2 S4 . Moreover, the close hierarchical structure of Cu7 S4 with ZnIn2 S4 and carrier separation facilitator of BPQDs were synergistically beneficial for boosting charge separation and transfer. The hydrogen production results showed that the ternary BPQDs@10% Cu7 S4 /ZnIn2 S4 yielded the highest H2 evolution rate of 885 μmol g −1 h −1, about 6.8 times higher than that of the pristine ZnIn2 S4, indicating its promising application in hydrogen production. In addition, the possible working mechanism was deeply explored using photo-electrochemistry, and the results illustrated that the enhanced photocatalytic hydrogen evolution can be attributed to the efficient charge separation caused by the formation of the hierarchical interface structure and increased carrier transfer efficiency of BPQDs. This study demonstrates that the regulation of interfacial charge transfer can positively facilitate photocatalytic activity and the ternary BPQDs@10% Cu7 S4 /ZnIn2 S4 can be employed as an efficient candidate for hydrogen production.